Rhetorical Structures of Introductions in Soft and Hard Science International Journals Written by Indonesian Scholars - Sahira Nurul Luthfianda; Eri Kurniawan; Wawan Gunawan (Yayasan Visi Intan Permata, 2021)
This study investigates the similarities and disparities of the rhetorical organizations of introduction sections in soft and hard science international journals written by Indonesian scholars and of the linguistic features employed to signal the moves. A corpus of ten introductions in the field of soft and hard science (five introductions each) was analyzed based on Swales' (2004) Create A Research Space (CARS) model. Findings were obtained through analyzing the moves and steps, as well as the linguistic realizations of the introductions. The analysis reveals that while Step 1 of Move 3 was an obligatory step, Step 1B of Move 2 and Step 2 of Move 3 were absent in both corpora. In addition, Step 1 of Move 2 was obligatory in soft science but was conventional in soft science corpus. Regarding linguistic features, the results show the influence of the different disciplines on the manifestation of metadiscoursal units (hedges and boosters) to enact the moves across the corpora, whereas no significant discrepancy was identified in the use of verb tense and sentence voice. The findings provide a better understanding of the rhetorical structure of research article introductions for and has pedagogical implications for the writing courses of Indonesian novice scholars.